2021
DOI: 10.1007/s12975-021-00947-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal n-3 Polyunsaturated Fatty Acid Enriched Diet Commands Fatty Acid Composition in Postnatal Brain and Protects from Neonatal Arterial Focal Stroke

Abstract: The fetus is strongly dependent on nutrients from the mother, including polyunsaturated fatty acids (PUFA). In adult animals, n-3 PUFA ameliorates stroke-mediated brain injury, but the modulatory effects of different PUFA content in maternal diet on focal arterial stroke in neonates are unknown. This study explored effects of maternal n-3 or n-6 enriched PUFA diets on neonatal stroke outcomes. Pregnant mice were assigned three isocaloric diets until offspring reached postnatal day (P) 10–13: standard, long-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
(63 reference statements)
2
9
0
Order By: Relevance
“…N-3 PUFA diet has been shown to increase the number of proliferating endothelial cells, length and number of vessels after stroke in aged mice (Cai et al, 2017). In recent neonatal mouse study, we showed that n-3 PUFA supplemented maternal diet decreased brain injury size in a model of neonatal stroke, suggesting a beneficial role in post ischemic inflammation and neuroprotection, while positive effects on neurovascular recovery were not studied and cannot be excluded (Chumak et al, 2022). To our knowledge, no other studies have assessed the effects of PUFA-supplemented maternal diet in the young or adult offspring in terms of cerebral vascular remodelling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…N-3 PUFA diet has been shown to increase the number of proliferating endothelial cells, length and number of vessels after stroke in aged mice (Cai et al, 2017). In recent neonatal mouse study, we showed that n-3 PUFA supplemented maternal diet decreased brain injury size in a model of neonatal stroke, suggesting a beneficial role in post ischemic inflammation and neuroprotection, while positive effects on neurovascular recovery were not studied and cannot be excluded (Chumak et al, 2022). To our knowledge, no other studies have assessed the effects of PUFA-supplemented maternal diet in the young or adult offspring in terms of cerebral vascular remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding cages were randomly assigned to one of the experimental isocaloric diets (AIN-93G, BioServ): standard (Stand, BioServ #S7628), n-3 long chain (LC)-PUFA enriched (n-3, BioServ #S7630; soybean oil replaced with Menhaden Fish oil) or n-6 LC-PUFA supplemented (n-6, BioServ #S7629; based on corn oil). The detailed composition of the diets is presented in our previous publication (Chumak et al, 2022). The day of birth was defined as postnatal day (P) 0.…”
Section: Diet and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…110 We showed that n3-PUFA enriched diet during gestation and postnatal period markedly changes lipid composition in brains of neonatal mice under physiological conditions and, interestingly, while it does not affect brain cytokine/chemokine levels under physiological conditions, n3-PUFA enriched diet mutes neuroinflammation and protects neonatal brain from stroke. 111 While the beneficial effects of lipid composition in protecting from acute injury in PAIS model are clear, the relative interplay of immune cells with dietary modifications during development and injury is not well understood.…”
Section: Lipid Signalingmentioning
confidence: 99%